Role of Psychological Stress and Choroidal Thickness in Central Serous Chorioretinopathy - Mathews, Reshmi; Horo, Saban; Jose, Deepa; Kavalakatt, Joel Antony; J, Grace Rebekah; John, Sheeja Susan (Nepalese Journal of Ophthalmology, 2023)
Introduction: Central serous chorioretinopathy (CSCR) is a disease with a multifactorial aetiology. Objectives: To evaluate the role of psychological stress and choroidal thickness in patients with CSCR.Materials and methods: This was a hospital-based, analytical cross-sectional study, conducted at Christian Medical College, Vellore, India, from 2018 February to 2019 September, after the approval of the Institutional Review Board and Ethics Committee. Patients who satisfied the eligibility criteria of the study, were selected from the outpatient clinics of the Department of Ophthalmology. Twenty-five patients with unilateral CSCR (Group 1 - cases), and 50 age and gender-matched patients without CSCR (Group 2 - controls), randomly selected in a 1:2 ratio, were enrolled after obtaining informed consent. Psychological stress was assessed using Cohen Perceived Stress Scale (PSS-10). All patients had a Swept Source optical coherence tomography scan of the macula. Subfoveal choroidal thickness (SFCT) of both eyes of all participants was measured using a standard protocol. The data were collated and analysed, using Independent samples t-test and Chi-square/ Fisher’s exact test, as appropriate, with IBM SPSS Statistics for Windows, version 21 (IBM Corp., Armonk, N.Y., USA). Results: There was a significant difference between the two groups in mean stress scores (p